Clinical Presentation, Causes, Treatment, and Outcome of Lip Avulsion Injuries in Dogs and Cats: 24 Cases (2001–2017) - Saverino, Kelly M.; Reiter, Alexander M. (Frontiers in Veterinary Science, 2018)
Lip avulsions are a common result of orofacial trauma in dogs and cats. Vehicular trauma and bite wounds are common causes. Surgical therapy is highly successful with early decontamination and tension-free closure. This retrospective case series assessed the signalment, causes, lesion location, treatment and outcome of lip avulsion injuries in dogs and cats. A total of 23 patients with 24 lip avulsion injuries were included in the study. They were comprised of 11 dogs and 12 cats. The patients were generally young, with 68.2% under three years of age and 36.4% under one year of age. The most common known causes were animal bites (26.1%) and vehicular trauma (21.7%). In cats, the most common cause was vehicular trauma (25%). In dogs, the most common cause was an animal bite (45.4%). Bilateral rostral upper lip avulsion was most common in dogs (36.3%), whereas bilateral rostral lower lip avulsion was most common in cats (53.8%). Concurrent injuries were frequent in both species with tooth fractures reported in 34.7%. All lip avulsion injuries were treated via wound debridement and lavage followed by appositional repair with absorbable suture material. The most common short-term complication was wound dehiscence (21.4%). Surgical therapy was highly successful with no significant long-term complications reported. The results suggest that lip avulsion injuries are primarily seen in younger dogs and cats, usually result from vehicular trauma or animal bites, and are successfully managed with surgical repair.